2016
DOI: 10.1038/nature17169
|View full text |Cite
|
Sign up to set email alerts
|

A map of the large day–night temperature gradient of a super-Earth exoplanet

Abstract: Over the past decade, observations of giant exoplanets (Jupiter-size) have provided key insights into their atmospheres, but the properties of lower-mass exoplanets (sub-Neptune) remain largely unconstrained because of the challenges of observing small planets. Numerous efforts to observe the spectra of super-Earths--exoplanets with masses of one to ten times that of Earth--have so far revealed only featureless spectra. Here we report a longitudinal thermal brightness map of the nearby transiting super-Earth 5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
330
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(360 citation statements)
references
References 43 publications
29
330
1
Order By: Relevance
“…Transits were subsequently detected by Winn et al (2011) using the MOST satellite, and Demory et al (2011) using the Spitzer Space Telescope. Winn et al (2011) find 55Cnce's mass, radius, and mean density to be 8.63±0.35 Å M , 2.00±0.14 Å R , and 5.9±1.5 g cm −3 , respectively, whereas Demory et al (2011) Gillon et al (2012), Dragomir et al (2014), and Demory et al (2016a), as well as from the ground by de Mooij et al (2014), report planet radius measurements in agreement with these studies. Altogether, their results suggest that, because 55Cnce's mean density is comparable to that of Earth, despite the greater mass (and consequently greater compression), the solid interior must be supplemented by a significant mass of water, gas, or other light elements.…”
Section: Cncesupporting
confidence: 75%
See 1 more Smart Citation
“…Transits were subsequently detected by Winn et al (2011) using the MOST satellite, and Demory et al (2011) using the Spitzer Space Telescope. Winn et al (2011) find 55Cnce's mass, radius, and mean density to be 8.63±0.35 Å M , 2.00±0.14 Å R , and 5.9±1.5 g cm −3 , respectively, whereas Demory et al (2011) Gillon et al (2012), Dragomir et al (2014), and Demory et al (2016a), as well as from the ground by de Mooij et al (2014), report planet radius measurements in agreement with these studies. Altogether, their results suggest that, because 55Cnce's mean density is comparable to that of Earth, despite the greater mass (and consequently greater compression), the solid interior must be supplemented by a significant mass of water, gas, or other light elements.…”
Section: Cncesupporting
confidence: 75%
“…However, follow-up secondary eclipse, phase-curve, and transit measurements (Demory et al , 2016a(Demory et al , 2016bRidden-Harper et al 2016;Tsiaras et al 2016), in conjunction with theoretical models (Lammer et al 2013;Ito et al 2015;Kite et al 2016), point to the existence of an envelope.…”
Section: Cncementioning
confidence: 99%
“…Observations and subsequent analysis of have shown that rocky planets, without thick protoatmospheres, are only found up to 1.5-2 R  in size (Dressing et al 2015;Marcy et al 2014;Rogers 2015;Weiss & Marcy 2014) with some recent observations indicating that rocky planets can reach ~1.9 R  in size (Buchhave et al 2016;Demory et al 2016). If most close-orbiting planets indeed form with thick protoatmospheres then the least massive planets must have lost their captured H2 and He (see Lopez and Rice (2016) for a discussion of atmospheric formation vs. atmospheric loss).…”
Section: -10mentioning
confidence: 99%
“…Notably, the three complementary methods all yielded the same conclusions, resulting in a mass measurement for the innermost planet that is not only precise but also robust. Demory et al 2011Demory et al , 2016Winn et al 2011;Nelson et al 2014), CoRoT-7b (Léger et al 2009;Queloz et al 2009;Haywood et al 2014), WASP-47e (Becker et al 2015;Dai et al 2015;Sinukoff et al 2017b;Vanderburg et al 2017), Kepler-78b (Howard et al 2013;Pepe et al 2013;Sanchis-Ojeda et al 2013;Hatzes 2014;Grunblatt et al 2015), Kepler-10b (Batalha et al 2011;Dumusque et al 2014;Weiss et al 2016;Rajpaul et al 2017), K2-131b , HD 3167b (Vanderburg et al 2016a;Christiansen et al 2017;Gandolfi et al 2017, respectively labeled as C17 and G17 in the plot), K2-106b (Guenther et al 2017;Sinukoff et al 2017a, G17 and S17 respectively). Notably, the last two planets have two independent density measurements that are not consistent with each other, resulting in a disagreement in the interpretation of the internal composition.…”
Section: Resultsmentioning
confidence: 99%